2007
DOI: 10.1110/ps.072801907
|View full text |Cite
|
Sign up to set email alerts
|

The three‐dimensional crystal structure of the PrpF protein of Shewanella oneidensis complexed with trans‐aconitate: Insights into its biological function

Abstract: In bacteria, the dehydration of 2-methylcitrate to yield 2-methylaconitate in the 2-methylcitric acid cycle is catalyzed by a cofactor-less (PrpD) enzyme or by an aconitase-like (AcnD) enzyme. Bacteria that use AcnD also require the function of the PrpF protein, whose function was previously unknown. To gain insights into the function of PrpF, the three-dimensional crystal structure of the PrpF protein from the bacterium Shewanella oneidensis was solved at 2.0 Å resolution. The protein fold of PrpF is striking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…The atomic coordinates and structure factors (codes 4IJZ and 4IK0) structure with dimerization occurring through the N-terminal domain (13)(14)(15)(17)(18)(19). Although previous studies of DAP epimerase suggest that the enzyme is monomeric (9,11,12), computational analyses of the crystal structures using Protein Interfaces, Surfaces and Assemblies (PISA) (20) suggest that the enzyme could adopt a dimeric architecture similar to the dimer observed in other DAP epimerase-like fold proteins.…”
Section: * This Work Was Supported In Part By Victorian Life Sciencesmentioning
confidence: 95%
See 1 more Smart Citation
“…The atomic coordinates and structure factors (codes 4IJZ and 4IK0) structure with dimerization occurring through the N-terminal domain (13)(14)(15)(17)(18)(19). Although previous studies of DAP epimerase suggest that the enzyme is monomeric (9,11,12), computational analyses of the crystal structures using Protein Interfaces, Surfaces and Assemblies (PISA) (20) suggest that the enzyme could adopt a dimeric architecture similar to the dimer observed in other DAP epimerase-like fold proteins.…”
Section: * This Work Was Supported In Part By Victorian Life Sciencesmentioning
confidence: 95%
“…Since the first structure of DAP epimerase was solved in 1998 (9), a number of structures have been determined that adopt the DAP epimerase-like fold. These include proline racemase (13), the isomerases PrpF (14,15) and 3-methylitaconate ⌬-isomerase (16), PhzF (17), and proteins of unknown or unconfirmed function (18,19). Interestingly, the majority of these proteins have been found to adopt a dimeric quaternary…”
Section: Diaminopimelate (Dap)mentioning
confidence: 99%
“…The enzyme is a symmetrical monomer comprised of two domains, each containing eight -strands and two -helices. This unique fold was first observed in H. influenzae DAP epimerase; since then, a number of proteins including a phenazine-biosynthetic protein (Blankenfeldt et al, 2004;Parsons et al, 2004), a proline racemase (Buschiazzo et al, 2006) and a methylaconitate isomerase (Garvey et al, 2007) have also been shown to adopt this fold.…”
Section: Introductionmentioning
confidence: 90%
“…These proteins have been used in both enzymatic and crystallographic studies which helps demonstrate the functionality of these plasmids (Garvey et al, 2007;Gray & Escalante-Semerena, 2007;Lewis & Escalante-Semerena, 2007;St Maurice et al, 2007).…”
Section: Use Of His 6 -Tev Vectors To Isolate the 2-methylaconitate Imentioning
confidence: 99%